Benchmarking Financial Development - Beck, Thorsten; Feyen, Erik; Ize, Alain; Moizeszowicz, Florencia (World Bank, Washington, DC, 2012)
Capitalizing on recent improvements in the availability of cross-country financial sector data, this paper proposes a standard methodology for benchmarking the policy component of financial development. Systematic controls are introduced to isolate main structural country characteristics and a principal components analysis is used to help identify a parsimonious set of ten "core" outcome indicators from a broader set of twenty seven potential indicators covering different dimensions of development in both financial institutions and financial markets. Such a broad-based approach helps reveal important determinants and regularities of the process of financial development. The paper also identifies some of the main data gaps that will need to be filled to allow further progress in financial benchmarking looking forward.